Distribusi Teripang (Holothuroidea) Pada Perairan Pesisir Nusa Lembongan, Kecamatan Nusa Penida, Kabupaten Klungkung, Bali - Deptson Baringin Silaen; I Wayan Arthana; Suprabadevi Ayumayasari Saraswati (Journal of Marine and Aquatic Sciences, 2018)
Sea cucumbers have a high economic potential and widely used by the community as food with nutrient content and high enough protein. The occurrence of an organism, including sea cucumbers in a waters is determined by the environmental factors of the waters, one of which is habitat. This study aims to determine the distribution of sea cucumbers (Holoturoidea) in the Coastal Waters of Nusa Lembongan, District Nusa Penida, Klungkung regency, Bali. This research was conducted in April-May 2017 in the Coastal Waters of Nusa Lembongan. This study looked at the distribution of sea cucumbers (Holoturoidea), substrate composition, physics-chemical parameters of waters (temperature, depth, salinity, pH, dissolved oxygen) and their relation to habitat conditions spread over Nusa Lembongan Coastal Waters. Data analysis in this study include the composition of sea cucumber, density of sea cucumber, the diversity of sea cucumber, and distribution of sea cucumbers. The results of the research conducted found 4 species of sea cucumber namely the type of Holothuria atra, Bohadchia vitiensis, Holothuria fuscocinerea and Holothuria sp. Physical-chemical parameters of the waters obtained in the research results are still categorized normal for the survival of sea cucumbers. Distribution of sea cucumbers during the study obtained by the results pattern of dispersal is clumped in all station with the index distribution value from 1.72 to 6.60.